Determinación De La Influencia De Las Fases Lunares, Utilizando Tres Variedades De Fréjol (Phaseolus Vulgaris L.) En El Cantón Antonio Ante, Provincia De Imbabura - Suárez, Maribel Vera; Batancourt, Ricardo Chávez; Molina, Víctor; Paredes, Joffre León; Contreras, Orlando Olvera; Álvarez, Hugo Alvarado; Guerrero, Luis Lahuasi (European Scientific Journal, ESJ, 2017)
The present study was conducted at the parish of San Roque, canton Antonio which is before the county of Imbabura. The seed materials used in this study are seeds of frijol varieties such as Paragachi, Canario, and Yunguilla which comes from Santa Catalina (INIAP). The treatments were made up of fréjol varieties (Phaseolus vulgaris L) through the use of the lunar calendar. It uses the design blocks totally at random (DBCA) with six treatments and four repetitions. Their variables were subjected to the variance analysis and it was used to determine the statistical differences of multiple ranges. The Tukey test was also used in this study. The development of the experimental rehearsal were carried out by the following works based on the analysis of the floor, preparation of the floor, subscriber, sowing, fertilization, watering, control of overgrowths, control Phytosanitary, and harvest. To estimate the effects of the treatments, the following data was collected: height from the plant to 30, 60, and 90 days after planting, days of flowering; days of maturation; longitude of sheaths; number of sheaths for plant; number of seeds forsheath; weigh of 100 seeds; grain yield; and economic analysis. According to the interpretation of the results, it was deduced that the biggest plant height was obtained by planting variety of Paragachi. This is done with the use of the lunar calendar. Also, the planting of variety of Yunguilla, using the agricultural lunar calendar, reported bigger number of sheaths for plant and seeds for sheath. The variable days of flowering and days of maturation shows a highly significant difference in the studied treatments. The biggest longitude of sheaths (14,55 cm); weigh of 100 seeds (73,25 g), and yield (3325,00 kg/ha) presented canario variety using lunar calendar. With regards to the economic analysis, all the treatments obtained profitable results. The canario variety stands out using the agricultural lunar calendar with a bigger net profit of 3274,14.